Epigenetic changes in the CDKN2A locus are associated with differential expression of P16INK4A and P14ARF in HPV-positive oropharyngeal squamous cell carcinoma - Schlecht, Nicolas F (Cancer Med, 2015)
Human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPSCC) is recognized as a distinct disease entity associated with improved survival. DNA hypermethylation profiles differ significantly by HPV status suggesting that a specific subset of methylated CpG loci could give mechanistic insight into HPV-driven OPSCC. We analyzed genome-wide DNA methylation of primary tumor samples and adjacent normal mucosa from 46 OPSCC patients undergoing treatment at Montefiore Medical Center, Bronx, NY using the Illumina HumanMethylation27 beadchip. For each matched tissue set, we measured differentially methylated CpG loci using a change in methylation level (M value). From these analyses, we identified a 22 CpG loci panel for HPV+ OPSCC that included four CDKN2A loci downstream of the p16(INK4A) and p14(ARF) transcription start sites. This panel was significantly associated with overall HPV detection (P < 0.05; ROC area under the curve = 0.96, 95% CI: 0.91–1.0) similar to the subset of four CDKN2A-specific CpG loci (0.90, 95% CI: 0.82–0.99) with equivalence to the full 22 CpG panel. DNA hypermethylation correlated with a significant increase in alternative open reading frame (ARF) expression in HPV+ OPSCC primary tumors, but not to the other transcript variant encoded by the CDKN2A locus. Overall, this study provides evidence of epigenetic changes to the downstream region of the CDKN2A locus in HPV+ oropharyngeal cancer that are associated with changes in expression of the coded protein products.